Calcineurin Antagonizes AMPK to Regulate Lipolysis in Caenorhabditis elegans - Yanli Wang; Cangsang Xie; Zhiqing Diao; Bin Liang (Molecules, 2017)
Calcineurin is a calcium- and calmodulin-dependent serine/threonine protein phosphatase, and the target of immunosuppressive agent tacrolimus (TAC). The dysfunction of calcineurin, or clinical applications of tacrolimus, have been reported to be associated with dyslipidemia. The underlying mechanisms of calcineurin and tacrolimus in lipid metabolism are largely unknown. Here, we showed that mutations of tax-6 and cnb-1, which respectively encode the catalytic subunit and the regulatory subunit of calcineurin, together with tacrolimus treatment, consistently led to decreased fat accumulation and delayed growth in the nematode Caenorhabditis elegans. In contrast, disruption of the AMP-activated protein kinase (AMPK) encoded by aak-1 and aak-2 reversed the above effects in worms. Moreover, calcineurin deficiency and tacrolimus treatment consistently activated the transcriptional expression of the lipolytic gene atgl-1, encoding triglyceride lipase. Furthermore, RNAi knockdown of atgl-1 recovered the decreased fat accumulation in both calcineurin deficient and tacrolimus treated worms. Collectively, our results reveal that immunosuppressive agent tacrolimus and their target calcineurin may antagonize AMPK to regulate ATGL and lipolysis, thereby providing potential therapy for the application of immunosuppressive agents.